TINJAUAN TEKNIS PENEMPATAN SISTEM MOORING BUOY DAN OBU INA-TEWS DI DASAR LAUT - Muhamad Irfan; Yudo Haryadi; Dwi Haryanto; Alfi Rusdiansyah (Oseanika, 2021)
[Technical Review of the Placement Mooring Buoy System and OBU Ina-TEWS on the Seabed] The development of tsunami early warning system technology has been carried out by BPPT since 2006. In addition to its development, BPPT has a duty in 2021 to install a tsunami early warning system in the ocean with a buoy platform using the Research Vessel Baruna Jaya BPPT as an ocean going survey vessel. The method of the placement a buoy platform on the seabed has to be well planned for the design, technical specifications, operational plans, and standard procedure of technical implementation. Because the buoy platform was manufactured at a high cost, and the survey operation requires a large amount of money, this system must be deployed in the ocean accurately using advanced marine survey technology. In addition, weather conditions have to be considered carefully because the location is on the open ocean. The state of ocean currents must also be carefully observed in order for the mooring buoy system to be properly installed, and the OBU system is able to detect sea level and communicate it to the surface buoy, which is subsequently send by satellite to the Ina-TOC data center in Jakarta. Keywords:      Ina-TEWS, marine survey, mooring system, buoy platform, research vessel, tsunami